Contingency and its consequences in Tristram Shandy by Laurence Sterne - Umerle, Tomasz (Journal of Education Culture and Society, 2020)
My paper proposes a new approach to the famous novel by Laurence Sterne TristramShandy. In my reading of this work I use the category of contingency which I define by referring to the German philosopher Odo Marquard and literary theories of a monographer of the contigency in literature and film Rafał Koschany. These are the basic inspirations for reflections on Tristram as a character, and simultaneously, narrator in the novel. In my view contingency manifests itself in Sterne's work in a two-fold manner it affects Tristram's life and narration. I will try to focus on the different ways in which these manifestations relate to each other.